Biodegradable polymer microspherse and crosslinked hyaluronic acid composite scaffold composition for breast tissue repair and regeneration
Patent Information
- Application Number
- KR1020260027349
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2046-02-11
Smart Images

Figure 112026018066654-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a composite support composition in which biodegradable polymer microspheres are dispersed in a cross-linked hyaluronic acid hydrogel, which can be used in an injectable medical device for filling and restoring the shape of breast tissue defects. Background Technology
[0002] After a mammotome procedure, known as a mastectomy for benign breast tumors, a cavity may form within the breast tissue, and if this cavity is not properly filled, a sunken deformity may occur after the procedure. Therefore, both the ability to immediately fill the cavity and correct the shape right after the procedure and the ability to maintain a natural breast shape over time are required.
[0003] Conventional breast filler materials include pure hyaluronic acid (HA) fillers (e.g., Macrolane used for breasts), PCL-based fillers for the face (e.g., PCL content of 30% by weight or more), and calcium (CaHA)-based fillers.
[0004] However, while hyaluronic acid-only fillers have excellent biocompatibility, they are relatively rapidly degraded by enzymes in the body. In areas with loose and large tissues, such as the breast, frequent migration—where the filler does not stay fixed at the injection site and flows down in the direction of gravity or spreads to surrounding areas—can reduce aesthetic satisfaction. Additionally, the duration of volume retention may be limited to 6 to 12 months.
[0005] In addition, while high-content biodegradable polymer fillers may be suitable for areas requiring firm support such as the nose or chin, they can cause a hard foreign body sensation or nodules in terms of the soft texture required for breast tissue, and due to their high viscosity, they require excessive pressure during injection, making them unsuitable for breast procedures that require fine manipulation.
[0006] In addition, radiopaque substances such as CaHA may appear as white dots during mammography (X-ray) for routine breast cancer screening, which can cause confusion with malignant microcalcification lesions and lead to misdiagnosis or unnecessary biopsies.
[0007] Meanwhile, most conventional fillers tend to be limited to the function of "filling" defects, and have limitations in that they do not sufficiently provide the function of achieving substantial tissue regeneration by inducing self-collagen production during the biodegradation process.
[0008] Therefore, there is a need for technological advancement in compositions for filling breast tissue defects that simultaneously satisfy immediate volume filling immediately after the procedure, stable fixation of the injection site (cohesion and internal mobility), viscoelasticity and a soft texture similar to breast tissue, radiolucency to exclude mammography diagnostic interference, and a tissue regeneration induction function that promotes self-collagen production during the biodegradation process. The problem to be solved
[0009] The present invention provides a composition that immediately fills the defect after a breast benign tumor excision procedure, ensures fixation at the injection site, provides a texture similar to breast tissue, ensures radiotransparency to eliminate diagnostic interference, and promotes self-collagen production during the biodegradation process to induce substantial tissue regeneration. means of solving the problem
[0010] To solve the above problem, the injectable composition according to the present invention is a composite scaffold composition for breast tissue repair and regeneration comprising a hydrogel matrix made of cross-linked hyaluronic acid and biodegradable polymer microspheres, wherein the biodegradable polymer microspheres exist in a dispersed state within the hydrogel matrix.
[0011] In one embodiment of the present invention, the composition can be injected into a defect site within breast tissue after a breast benign tumor excision procedure to fill the defect space, prevent depression deformation, and induce self-tissue regeneration.
[0012] The above-mentioned cross-linked hyaluronic acid hydrogel may be cross-linked using one or more of 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether (PEGDE), polypropylene glycol diglycidyl ether, divinyl sulfone (DVS), 1,2,7,8-diepoxyoctane, and epichlorohydrin, and preferably BDDE may be used.
[0013] In one embodiment of the present invention, the average molecular weight of the hyaluronic acid used as a raw material for the cross-linked hyaluronic acid hydrogel may be in the range of 1,000 Da (1 kDa) to 20,000,000 Da (20 MDa).
[0014] In one embodiment of the present invention, the hyaluronic acid concentration of the cross-linked hyaluronic acid hydrogel may be in the range of 0.1 mg / mL to 300 mg / mL.
[0015] In one embodiment of the present invention, the biodegradable polymer microsphere may be selected from one or more of the group consisting of polycaprolactone (PCL), polylactic acid (PLA), polyglycolic acid (PGA), poly(lact-co-glycolic) acid (PLGA), polydioxanone (PDO), polytrimethylene carbonate (PTMC), polyanhydride, polyorthoester, and copolymers thereof, and preferably polycaprolactone may be used.
[0016] In one embodiment of the present invention, the biodegradable polymer microspheres may be spherical particles with a diameter ranging from 10 μm to 100 μm, considering ease of injection and biocompatibility.
[0017] In one embodiment of the present invention, the biodegradable polymer microspheres are included in a range of 8% to 28% by weight relative to the total weight of the composition, depending on the depth of the application site and the desired support force, and the cross-linked hyaluronic acid hydrogel may be included in a range of 72% to 92% by weight relative to the total weight of the composition, and preferably, 15% by weight of microspheres and 85% by weight of hydrogel may be included.
[0018] In one embodiment of the present invention, the storage modulus (G') of the composition can be adjusted in the range of 200 Pa to 800 Pa at 25°C depending on the injection depth and the desired volume retention force.
[0019] In one embodiment of the present invention, when the composition is filled into a 1 mL syringe and then extruded at a speed of 10 mm / min using a 23G cannula, the injection pressure can be adjusted in the range of 8 N to 25 N depending on the convenience of the procedure and the application site. Effects of the invention
[0020] The present invention optimizes the PCL content to a level of 15% by weight, thereby simultaneously ensuring softness suitable for breast tissue and ease of procedure. Additionally, the microspheres act as a support within the hydrogel network, inhibiting migration after injection through high cohesion. Furthermore, they exhibit radiotransparency similar to surrounding tissues during mammography, thereby reducing diagnostic interference. Moreover, even after HA is absorbed in vivo, volume maintenance and tissue regeneration can be induced through collagen production around the PCL microspheres. Brief explanation of the drawing
[0021] Figure 1 is a drawing of selected PCL microspheres taken with an SEM. Figure 2 is a graph comparing the rheological properties and injection force according to the PCL microsphere content of the composition. Figure 3 is a diagram comparing the radiotransparency of the composition of the present invention, a CaHA filler, and a hyaluronic acid filler that does not contain PCL microspheres. Figure 4 is a diagram comparing the cohesive force of the composition of the present invention and a hyaluronic acid filler that does not contain PCL microspheres by stirring. Figure 5 shows the results of analyzing the tissue by Masson's Trichrome staining after 12 weeks of injecting the composition of the present invention and a hyaluronic acid filler not containing PCL microspheres into experimental rats. Specific details for implementing the invention
[0022] The core composition of the present invention is a two-component composite system of biodegradable polymer microspheres and cross-linked hyaluronic acid hydrogel. The biodegradable polymer microspheres are spherical particles with a diameter of 20 to 50 μm containing polycaprolactone (PCL), and are included in an amount of 8 to 28 weight% relative to the total weight of the composition, preferably 15 weight% relative to the total weight of the composition. The cross-linked hyaluronic acid hydrogel is a hydrogel modified to have viscoelasticity by cross-linking with a crosslinking agent (e.g., BDDE), and is included in an amount of 72 to 92 weight% relative to the total weight of the composition, preferably 85 weight% relative to the total weight of the composition, and serves as a carrier that uniformly disperses the microspheres.
[0023] In the present invention, the composition of microspheres : cross-linked HA = 15 wt% : 85 wt% is an optimized composition intended to ensure softness similar to breast tissue and ease of procedure, while simultaneously allowing the microspheres to act as physical cross-linking points and supports within the hydrogel network, thereby exhibiting higher cohesion and positional stability compared to HA alone. Furthermore, through the optimization of the composition and mixing ratio, radiotransparency indistinguishable from surrounding tissues is achieved during X-ray imaging, thereby fundamentally eliminating the risk of misdiagnosis.
[0024] The average molecular weight of hyaluronic acid affects injectability, retention, elasticity, and degradation rate, so it can be selected according to the desired physical properties, for example, in the range of about 0.001 MDa to 20 MDa (1 kDa to 20,000 kDa). Preferably, high molecular weight hyaluronic acid in the range of 0.5 MDa to 5.0 MDa may be used to ensure elasticity and retention, and in one embodiment, hyaluronic acid with a molecular weight of 2.5 MDa is used.
[0025] It is desirable for the hydrogel matrix to be designed to be viscoelastic so that it can be pressurized and extruded through a syringe or injection device, and it is desirable for it to have both cohesiveness and elasticity so that it can be properly distributed within the tissue without excessive diffusion.
[0026] The crosslinking reaction is performed to form a three-dimensional network structure using the hydroxyl groups of the hyaluronic acid chain as reaction sites. The crosslinking agent may include one or more selected from 1,4-butanediol diglycidyl ether (BDDE), ethylene glycol diglycidyl ether (EGDGE), 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether (PEGDE), polypropylene glycol diglycidyl ether, divinyl sulfone (DVS), 1,2,7,8-diepoxyoctane, epichlorohydrin, or combinations thereof, and preferably 1,4-butanediol diglycidyl ether (BDDE) is used. BDDE reacts with the hydroxyl groups of hyaluronic acid chains to form ether bonds, thereby forming a cross-linked structure that forms a three-dimensional network structure.
[0027] When using BDDE, a method can be applied in which hyaluronic acid is dissolved under alkaline conditions, BDDE is added, and the mixture is reacted at a specific temperature for a specific period of time. During the reaction process, ether bonds are formed between hyaluronic acid chains, allowing the solution to gradually convert into a gel form. The amount of BDDE used can be set to a range of 0.001 to 0.01 based on the molar ratio to the hyaluronic acid repeating unit to control the degree of crosslinking and the storage modulus (G') of the final gel. The crosslinking conditions can be controlled by temperature, time, pH, the amount of crosslinking agent added, and the concentration of hyaluronic acid, and it is desirable to adjust them to meet the targets for the injectability and tissue retention of the final composition.
[0028] A cross-linked hyaluronic acid hydrogel is prepared according to the following process. First, sodium hyaluronate with the above average molecular weight range is dissolved in deionized water or an alkaline aqueous solution. The concentration of the hyaluronic acid aqueous solution prior to the cross-linking reaction can be widely adjusted according to the physical properties of the desired hydrogel and the cross-linking efficiency, for example, to be in the range of about 0.1 mg / mL to 300 mg / mL. Considering the dissolution efficiency and uniform mixing in the process, it may preferably be in the range of 5 mg / mL to 50 mg / mL, and more preferably in the range of 10 mg / mL to 30 mg / mL. For example, 2.0 g of sodium hyaluronate with an average molecular weight of about 2.0 MDa is dissolved in 100 mL of deionized water to prepare a hyaluronic acid solution with a concentration of about 20 mg / mL. Next, in order to ensure crosslinking reaction efficiency, the pH of the solution is adjusted to a range of about 10.0 to 12.0, more specifically to a level of about pH 11.0 using an NaOH solution or the like.
[0029] If the HA concentration is excessively low, the average distance and contact frequency between hyaluronic acid chains in the solution increase, which reduces the probability of the crosslinking agent connecting the hyaluronic acid chains, and the actual crosslinking efficiency may decrease even under the same amount of crosslinking agent and reaction conditions. If connections between HA chains are not sufficiently formed, the three-dimensional network density decreases, and the dynamic modulus (G') and cohesiveness of the final hydrogel may fall short of the target values. Furthermore, there may be a tendency for reduced shape stability or excessive diffusion within the tissue after injection. Additionally, under dilution conditions, the solid content of the gel produced after the reaction is low, which may lead to excessive volume expansion or increased processing time during washing, dialysis, and concentration, thereby reducing process efficiency. Moreover, variations in physical properties may widen during the concentration process, leading to reduced reproducibility between batches. Furthermore, if the reaction is carried out in a diluted state, a relative excess of the crosslinking agent may be formed within the reaction system; therefore, unless the amount of crosslinking agent is adjusted to achieve the target properties, problems may arise in which the burden of managing residual crosslinking agent increases.
[0030] When the HA concentration is excessively high, the viscosity of the aqueous solution increases rapidly, making it difficult to mix for the uniform dispersion of crosslinking agents such as BDDE. This can lead to the formation of a heterogeneous crosslinked structure where areas of localized concentration of the crosslinking agent coexist with areas lacking the agent. Non-uniform mixing can consequently result in heterogeneity of the microstructure within the gel, the formation of localized high-crosslinked clumps, and increased variation in physical properties within a batch. This can lead to reduced usability, such as increased syringe extrusion force, increased injection resistance, and a lumpy sensation or uneven distribution during injection. In reaction systems with excessively high viscosity, it is difficult to maintain a uniform distribution of reaction heat and temperature. Since the reaction rate varies by location, regions of over- or under-progression of the crosslinking reaction may occur, resulting in products that fall outside the target G' range. Furthermore, under high concentration conditions, dissolution itself may be incomplete, leaving undissolved particles or fine aggregates. These can cause filtration and filling defects, air bubble incorporation, and increased variability in quality inspection during subsequent homogenization and sterile filling processes. Consequently, high-concentration conditions may make it difficult to ensure manufacturing reproducibility due to increased equipment load and increased difficulty in process control.
[0031] Therefore, in the present invention, by simultaneously considering dissolution efficiency, mixing uniformity, crosslinking efficiency, and the viscoelasticity and injectability of the final hydrogel, setting the HA concentration before the crosslinking reaction to the above-mentioned preferred range is an advantageous configuration in terms of manufacturing reproducibility and product performance.
[0032] Subsequently, a crosslinking agent is added to the hyaluronic acid solution. The amount of crosslinking agent used can be adjusted according to the degree of modification and viscoelasticity of the target hydrogel, and can be set to a range of about 0.01 to 20 mol% (or 0.001 to 0.2 molar ratio) based on the molar ratio to the hyaluronic acid repeating unit. Considering crosslinking efficiency and biosafety, it is preferably set to a range of 0.1 to 10 mol%, and more preferably to a range of 0.2 to 2.0 mol%. Within this range, the degree of modification and the elastic modulus (G') of the final gel can be controlled. For example, a gel with an appropriate degree of modification can be formed by adding about 40 μL of BDDE to 100 mL of a hyaluronic acid solution at a concentration of 20 mg / mL. After adding the crosslinking agent, the reaction is carried out at a temperature in the range of about 30 to 60°C, for example, about 45 to 50°C, for about 1 to 5 hours. As the reaction proceeds, the hyaluronic acid solution gradually turns into a gel state, and finally, a hyaluronic acid hydrogel having a three-dimensional crosslinked structure is formed. At this time, the reaction time and temperature can be appropriately adjusted according to the elastic modulus (G') and viscosity to be finally obtained.
[0033] The crosslinking agent content can be adjusted according to the application of the hydrogel. For use in increasing volume in the deep layers of the face, the ratio of the crosslinking agent can be set somewhat higher to have a relatively high G', and for use in improving fine wrinkles, the ratio of the crosslinking agent can be lowered to have a lower G'.
[0034] Since the elastic modulus (G') of cross-linked hyaluronic acid hydrogel is a viscoelastic indicator directly related to injection suitability and shape stability within tissue, the elastic modulus (G') of cross-linked hyaluronic acid hydrogel can be adjusted according to the skin layer to be injected (upper dermis, lower dermis, subcutaneous layer, etc.) and the application site, and can be widely adjusted, for example, in the range of greater than 200 Pa and less than 800 Pa.
[0035] If G' is excessively low, the hydrogel's elastic network is relatively weak, leading to reduced shape retention within the tissue after injection and insufficient retention, which can result in excessive diffusion. In this case, the substance tends to spread to surrounding tissues rather than remaining locally at the injection site, making it difficult to maintain concentration at the target area. Consequently, the sustainability of moisturization or microenvironment improvement may decrease, or the duration of expected efficacy may be shortened. Furthermore, if the hydrogel's cohesiveness is low, the discharge pattern from the needle tip may become unstable during the injection process. This can lead to increased backflow or leakage after injection, potentially causing the actual delivery volume to be lower than intended. Moreover, in applications requiring mechanical support within the tissue (e.g., contour correction, localized volume support), a low G' may result in difficulty maintaining shape and weakened corrective effects due to insufficient support.
[0036] If G' is excessively high, the stiffness of the hydrogel increases, which may lead to an excessive increase in extrusion force and injection resistance during injection. This can result in reduced syringe handling, increased operator fatigue, limitations in needle gauge, and increased injection pain. Furthermore, when injecting into shallow layers (e.g., the upper dermis), there may be an increased risk of tissue damage or non-uniform injection. Additionally, high G' reduces dispersibility within tissues, which may result in localized lumpiness or an increased tactile foreign body sensation. In superficial or thin skin areas, there may be an increased likelihood of nodularity, irregular contours, or surface visibility. Moreover, excessive network stiffness can cause mechanical discrepancies with the natural movement of tissues, thus increasing the likelihood of alienation or discomfort in areas with significant movement.
[0037] The elastic modulus of the composition of the present invention for breast tissue repair and regeneration may be in the range of 200 Pa to 800 Pa depending on the injection depth and the desired volume retention capacity, and preferably in the range of 400 Pa to 500 Pa. The above range can be achieved by a combination of hyaluronic acid solid content concentration (e.g., in the range of 0.5 mg / mL to 100 mg / mL) and the degree of crosslinking, and is preferably understood as a design range considering suitability for intradermal injection.
[0038] Storage modulus can be controlled by changing the content of microspheres within the hydrogel; the higher the microsphere content, the higher the storage modulus. If the storage modulus is low at 200 Pa or lower, it is difficult to structurally support the defect space, raising concerns that it may spread easily, while if the storage modulus is high at 800 Pa or higher, there is a high likelihood of a hard foreign body sensation.
[0039] The elastic modulus (G') can be controlled by crosslinking conditions, and in particular, the amount of crosslinking agent, reaction time, and reaction temperature can be utilized as key factors affecting the elastic modulus (G') of the final gel. For example, increasing the molar ratio of the crosslinking agent or increasing the reaction time can increase the degree of crosslinking, thereby enabling control in the direction of increasing G'; conversely, decreasing the molar ratio of the crosslinking agent or shortening the reaction time can enable control in the direction of decreasing G'. In this case, it is desirable to control the degree of crosslinking and the elastic modulus (G') of the final gel by controlling the amount of crosslinking agent within the range of approximately 0.01 to 20 mol% based on the molar ratio to the hyaluronic acid repeating unit. Furthermore, increasing the concentration of hyaluronic acid solids in the hydrogel increases the network density, thereby enabling control in the direction of increasing G'; and decreasing the concentration of solids enables control in the direction of decreasing G'; therefore, it is desirable to optimize both the hyaluronic acid concentration and the crosslinking conditions together.
[0040] If the measured G' deviates from the target range as described above, feedback control toward the target properties is possible by adjusting the molar ratio of the crosslinking agent, reaction time, or reaction temperature during the crosslinking reaction step, or by adjusting the concentration of hyaluronic acid solids during the step after washing and concentration. Additionally, since the homogenization process can affect the microstructure and texture that determine injectability, it is desirable to configure the homogenization conditions to be managed by considering the balance of extrusion force, viscosity, and distribution behavior within the tissue, even within the same G' range.
[0041] After the crosslinking reaction is completed, the formed gel is cut into blocks of appropriate size and repeatedly immersed and washed in a large amount of purified water or isotonic buffer solution to remove residual crosslinking agent and low molecular weight by-products. Generally, it is desirable to wash at least four times using a washing solution equivalent to at least 10 times the total gel volume, and to continue washing while replacing the washing solution until the residual crosslinking agent is reduced to below the analytical limit. If necessary, unreacted crosslinking agent and low molecular weight impurities can be further removed by dialyzing for 1 hour to 168 hours (7 days) using a dialysis membrane with a molecular weight cutoff limit (MWCO) in the range of about 1 kDa to 1,000 kDa (1 MDa). Considering process efficiency and degree of purification, the process is preferably performed for 6 to 72 hours using a dialysis membrane with a molecular weight cutoff limit of 3.5 kDa to 100 kDa, and more preferably for 12 to 48 hours using a membrane of 10 kDa to 50 kDa. After the washing and dialysis processes are completed, the gel is concentrated or dehydrated to adjust the hyaluronic acid solid content concentration to a range of about 0.5 mg / mL to 100 mg / mL. Preferably, for use as a skin booster, the concentration may be in the range of 1 mg / mL to 10 mg / mL, and for use as a volume-enhancing filler, it may be adjusted to a range of 15 mg / mL to 30 mg / mL. In one embodiment of the present invention, the concentration is adjusted to a level of about 20 mg / mL to provide a filler base that is injectable and has sufficient shape stability.
[0042] As the cross-linked hyaluronic acid gel purified and concentrated as described above may exist in a highly viscoelastic mass state, a mechanical homogenization process is performed to convert it into a homogeneous gel state that is easy to use. For example, the gel is repeatedly passed through a plunger-type kneader or a screw-type homogenizer while applying shear force to form gel particles with a size of tens to hundreds of micrometers. In this process, each particle intertwines with others to maintain a continuous gel phase while possessing a homogeneous texture sufficient to pass through a syringe. It is desirable to perform the homogenization process under vacuum or reduced pressure whenever possible to minimize the generation of internal bubbles.
[0043] The above-mentioned biodegradable polymer microspheres may comprise polycaprolactone (PCL), but are not limited thereto, one or more selected from the group consisting of polylactic acid (PLA), polyglycolic acid (PGA), poly(lactic-co-glycolic acid) (PLGA), polydioxanone (PDO), polytrimethylene carbonate (PTMC), polyanhydrides, polyorthoesters, and copolymers thereof. However, most preferably, polycaprolactone (PCL) is used for long-term volume retention and flexibility.
[0044] PCL microspheres are prepared using an O / W emulsification and solvent evaporation method. An oil phase is prepared by dissolving PCL (Mw 80,000) in dichloromethane (DCM) at a concentration of 10 wt%, and a water phase is prepared by slowly adding the oil phase dropwise while rotating a homogenizer at 5,000 rpm to form an O / W emulsion. Subsequently, the microspheres are cured by stirring at room temperature for 4 hours to completely volatilize the DCM. The obtained microspheres are then washed with distilled water at least 5 times, freeze-dried, and selected to contain only microspheres in the range of 20 to 50 μm using a standard sieve.
[0045] Specifically, in the step of preparing a biodegradable polymer PCL (Mw 80,000) and preparing the oil phase solution in a dichloromethane (DCM) organic solvent, the concentration of polycaprolactone (PCL) can be adjusted to a range of 1% to 35% by weight relative to the organic solvent. Considering the uniform spherical formation of particles and production yield, the oil phase solution is prepared by dissolving in a range of preferably 5% to 20% by weight, and more preferably 8% to 15% by weight (e.g., 10% by weight). Considering the volatility and toxicity of DCM, the dissolution operation is performed in a hood environment with adequate ventilation, and the dissolution is performed using a magnetic stirrer or a roller mixer. The completion of dissolution is determined by the visual absence of solids and the securing of homogeneous transparency of the solution.
[0046] In the step of preparing the above water phase, the emulsifier may use one or more selected from the group consisting of polysorbate (e.g., Tween 20, Tween 80), polyvinylpyrrolidone (PVP), methylcellulose (MC), gelatin, polyethylene glycol (PEG), and mixtures thereof, including but not limited to polyvinyl alcohol (PVA), and preferably polyvinyl alcohol is used.
[0047] The concentration of the above emulsifier can be adjusted to a range of 0.1% (w / v) to 10% (w / v) relative to the total aqueous phase, and considering particle dispersion stability and washing efficiency, a range of 0.5% to 5% (e.g., 1%) is preferably appropriate. In addition, the volume of the aqueous phase can be set to have a volume ratio of 3 to 50 times the volume of the oil phase solution, and preferably used in a range of 5 to 20 times to ensure the stability of the O / W emulsion.
[0048] The above "1% PVA aqueous solution" can typically be prepared on a w / v basis. For example, PVA can be dispersed in purified water, completely dissolved by heating and stirring, and then cooled to room temperature for use. Factors that reduce emulsion stability can be reduced by removing bubbles from the aqueous solution before emulsification (decompression degassing or settling).
[0049] The above aqueous phase is introduced into a reaction vessel and stirred using a homogenizer. At this time, the rotation speed can be adjusted within the range of 1,000 rpm to 15,000 rpm to ensure stable formation of the emulsion and control of the target particle size. However, to suppress the generation of nanoparticles due to excessive shear force or the generation of large particles due to insufficient shear force, and to maximize the yield, the rotation is preferably set within the range of 2,000 rpm to 10,000 rpm, and more preferably within the range of 3,000 rpm to 7,000 rpm (e.g., 5,000 rpm).
[0050] Since a rise in temperature during emulsification can affect particle size distribution and solvent volatilization behavior, cooling water circulation or an ice bath is applied to the outside of the reaction vessel to stabilize the temperature within the room temperature range. The effective capacity of the reaction vessel is 500 mL of aqueous phase, with a margin capacity to prevent overflow and splashing.
[0051] With the homogenizer rotating at 5,000 rpm, the oil phase solution is slowly dropped to ensure emulsion stability and facilitate the formation of a target particle size (20–50 μm), thereby forming an O / W (Oil-in-Water) emulsion. As an example, the dropping speed can be maintained constant using a dropping funnel, a syringe, or a metering pump. The configuration increases the efficiency of forming fine oil phase droplets by maintaining a constant rotation speed of the homogenizer during dropping and positioning the oil phase dropping location close to the shear region of the homogenizer. Even after dropping is finished, shear mixing is maintained for a certain period of time to ensure the homogeneity of the emulsion.
[0052] When applying the solvent evaporation method to the formed emulsion, the stirring temperature can be adjusted within the range of 5 to 50 °C to control the solvent volatilization rate and the curing behavior of the polymer. Considering the boiling point of DCM (approx. 40 °C) and the melting point of PCL (approx. 60 °C), the process is preferably performed within the range of 15 to 40 °C (e.g., room temperature) to prevent rapid roughening of the particle surface and maintain sphericity. Additionally, the stirring time can be adjusted within the range of 30 minutes to 24 hours depending on the solvent removal efficiency and production scale. To minimize residual solvent and ensure particle strength, the process is preferably performed for 2 to 10 hours (e.g., 4 hours) to completely volatilize the DCM and fully cure the PCL microspheres. Furthermore, to increase solvent removal efficiency, vacuum or gas purging conditions may be applied in addition to simple stirring.
[0053] The aforementioned "stirring" is performed to suppress droplet aggregation after emulsification and to promote the continuous diffusion and evaporation of the solvent. Since the complete volatilization of DCM is a key requirement for reducing residual solvent, the driving force for volatilization is typically increased by maintaining open conditions within the hood, ensuring airflow, and applying reduced pressure conditions if necessary. The completion of curing can be determined based on changes in physical behavior, such as the spherical formation of particles within the suspension and a decrease in tackiness.
[0054] To obtain microspheres after curing, an operation to separate solids from the suspension is performed. The separation method can be selected from centrifugation or filtration, and filter pore size or centrifugation conditions are set according to the particle size range to reduce microsphere loss. After the microsphere separation, the supernatant is removed to perform pretreatment for the removal of residual PVA and trace solvents.
[0055] To remove residual PVA and aqueous components, the obtained microspheres are washed with distilled water at least five times. Each washing cycle is implemented by repeating "redispersion-separation-supernatant removal," and the washing end criteria can be set based on a reduction in foaming of the supernatant, a reduction in viscosity, or a reduction in other residual emulsifier indicators.
[0056] Washed microspheres are freeze-dried to obtain a dry powder. Before freeze-drying, the microspheres are frozen, and sublimation drying is performed under reduced pressure while frozen to reduce moisture and residual solvent. After freeze-drying, the fluidity and aggregation of the powder are checked to ensure the reproducibility of the subsequent sieving process.
[0057] Freeze-dried microspheres are selected for particle size using a standard sieve. At this time, the average particle size of the microspheres can be selected in the range of 10 µm to 100 µm to control ease of injection and in vivo degradation behavior. However, to prevent excessive phagocytosis caused by particles smaller than 10 µm and to prevent needle clogging and foreign body sensation caused by particles larger than 100 µm, microspheres are preferably selected and used in the range of 15 µm to 80 µm, and in the optimal range of 20 µm to 50 µm to achieve a soft tactile sensation of breast tissue.
[0058] As an example, the screening method involves stacking a 100 µm sieve and a 10 µm sieve and then performing vibrating sieving, and recovering the fraction remaining on the 10 µm sieve as a target fraction while passing through the 100 µm sieve. Fractions exceeding 100 µm and fractions less than 10 µm, other than the target fraction, can be separated for disposal or reprocessing (re-emulsification, etc.).
[0059] When the particle size becomes too small, less than 10 μm, the volume-to-surface area ratio of the microspheres increases, leading to a dominance of microparticle behavior within the aqueous or hydrogel matrix. This increases micro-dispersion or diffusion within the target site after injection, raising concerns that positional stability may be reduced. Additionally, as the fraction of small particles increases, the number of particles per unit weight increases excessively, making it difficult to maintain a uniform dispersion state within the hydrogel. Furthermore, in some embodiments, there may be an increased likelihood of hypersensitive tissue reactions in the body or long-term nodular tactile changes.
[0060] Conversely, if the particle size exceeds 100 μm, inter-particle interference and bridging phenomena increase within the flow paths of the cannula or syringe, raising concerns about blockage or increased injection force during the injection process. Additionally, sedimentation due to gravity or local aggregation increases within the hydrogel matrix, potentially leading to greater deviation in particle distribution within the composition. Furthermore, an increase in the fraction of oversized particles may result in a rougher texture or increased local foreign body sensation at the injection site, and in the long term, there is a possibility of increased risk of local fibrosis or nodule formation due to non-uniformity in tissue reactions surrounding the microspheres.
[0061] Therefore, the configuration of securing a target fraction in the range of 10 to 100 μm through standard sieve screening is a manufacturing management configuration for maintaining the injectability and quality reproducibility of the composite scaffold composition and for reliably achieving the soft touch and positional stability required for application to breast tissue.
[0062] Figure 1 is a photograph of selected microspheres observed with an SEM. The condition of the selected microspheres is examined using SEM observation or particle size analysis equipment to confirm sphericity, surface condition, and particle size distribution. Since residual solvents and residual emulsifiers are subject to management in terms of product safety and regulatory compliance, the presence of residual solvents and emulsifiers is checked.
[0063] The preparation of a composite composition using cross-linked HA hydrogel and PCL microspheres is carried out by a process of preparing a pre-prepared cross-linked HA hydrogel and selected PCL microspheres, and then quantifying and mixing each. At this time, the cross-linked HA hydrogel is quantified to 72 to 92 weight%, preferably 85 weight%, and the PCL microspheres are quantified to 8 to 28 weight%, preferably 15 weight%.
[0064] When the microsphere content is 8% by weight or less, the storage modulus is low at 200 Pa or less, making it difficult to structurally support the defect space and raising concerns that it may spread easily; conversely, when the microsphere content is 28% by weight or more, the storage modulus is high at 800 Pa or more, making it highly likely that a hard foreign body sensation will be felt. On the other hand, a composition containing 15% by weight of PCL microspheres exhibits an optimal elastic range of 400 to 500 Pa, which is advantageous for application to breast tissue.
[0065] The injection pressure is preferably 8 to 25 N depending on the ease of procedure and the application site. Compositions with a microsphere content of 30% by weight or more require an excessive force of 25 N or more when injected, whereas compositions with a PCL microsphere content of 15% by weight exhibit ease of procedure suitable for general filler procedures at a level of 8 to 25 N.
[0066] In the above quantitative process, since the cross-linked HA hydrogel has high viscoelasticity and tends to adhere to the inner wall of the container, it is repeatedly cut and transferred using a spatula or the like to ensure that no residue remains on the inner wall of the quantitative container or mixing container, and the weight is adjusted to the target mass through zero-point correction of the container weight. In addition, since PCL microspheres are in the form of fine powder or granules and may be lost due to scattering or electrostatic adhesion, a weighing tray or a sealed weighing container is used to reduce loss and adjust to the target mass.
[0067] The quantified cross-linked HA hydrogel and PCL microspheres are placed into the mixing container of a vacuum mixer, and then low-speed mixing is performed using the vacuum mixer to suppress bubble generation.
[0068] In the above mixing process, the stirring speed can be widely adjusted in the range of 10 rpm to 2,000 rpm depending on the viscosity of the hydrogel and the impeller shape of the mixing equipment. For low-speed mixing conditions to suppress bubble generation and prevent microsphere breakage, a range of 20 rpm to 100 rpm (e.g., 50 rpm) is preferred, and when large-volume production or high-shear dispersion is required, it can be set in the range of 100 rpm to 1,000 rpm. In addition, the mixing time can be adjusted in the range of 5 minutes to 300 minutes (5 hours) to ensure uniform dispersion. Considering production efficiency and prevention of degradation of physical properties (such as HA chain breakage), the process is preferably performed for a range of 10 minutes to 120 minutes, and more preferably for 20 minutes to 60 minutes (e.g., 30 minutes) so that PCL microspheres are uniformly dispersed within the HA hydrogel.
[0069] In the above mixing process, "uniform dispersion" is determined based on a state in which the density difference of microspheres observed in the upper, middle, and lower parts of the mixture is substantially reduced, and non-uniform patterns in the form of clusters or stripes where microspheres are locally aggregated are not substantially observed. In addition, if microspheres accumulate locally around the walls or impeller during mixing, the mixing conditions are maintained to minimize blind spots in the mixing area within the limits allowed by the device structure to ensure final homogeneity.
[0070] Since residual bubbles in the composition after mixing is complete may affect the product appearance and injection behavior, a method to reduce bubbles in the mixture may be applied by maintaining vacuum stirrer usage conditions or through a separate reduced pressure maintenance process. This bubble reduction process may be included in an embodiment that embodies the manufacturing concept of using a vacuum stirrer "to prevent bubble generation."
[0071] The composite composition prepared as described above is filled into a 10 mL syringe to complete the final prototype. In the syringe filling process, the composition is continuously transferred into the syringe barrel to suppress air entrainment, and if necessary, the presence of bubbles is checked during the filling process; if bubbles are observed, a removal operation is performed, and then the syringe is sealed.
[0073] [Example 1]
[0074] For the preparation of the hyaluronic acid hydrogel, sodium hyaluronate with a molecular weight of 2.5 MDa was dissolved in an alkaline aqueous solution, and then BDDE (1,4-butanediol diglycidyl ether), a crosslinking agent, was added and a crosslinking reaction was performed at 30°C. Subsequently, residual crosslinking agent was removed through washing and dialysis processes, and a crosslinked hyaluronic acid hydrogel with a final concentration of 20 mg / mL was obtained.
[0075] For the preparation of PCL microspheres, first, an oil phase solution was prepared by dissolving PCL (Mw 80,000), a biodegradable polymer, in a dichloromethane (DCM) organic solvent at a concentration of 10 wt%, and 500 ml of a 1% PVA (Polyvinyl alcohol) aqueous solution (Water phase) was prepared as an emulsifier, and the oil phase solution was slowly added dropwise while rotating a homogenizer at 5,000 rpm to form an O / W (Oil-in-Water) emulsion.
[0076] The generated O / W emulsion was cured by completely evaporating the organic solvent (DCM) from the organic solvent using the solvent evaporation method at room temperature for 4 hours while stirring. The cured microspheres were washed with distilled water at least 5 times, freeze-dried, and sieved to obtain only microspheres with a particle size in the range of 20 to 50 μm.
[0077] 85g of the cross-linked HA hydrogel produced above and 15g of the selected PCL microspheres were weighed and mixed in a vacuum mixer at a low speed (50 rpm) for 30 minutes to prevent the generation of bubbles, thereby producing a final composite support in which the PCL microspheres were uniformly dispersed within the HA hydrogel, and then the prepared composition was filled into a 10mL syringe.
[0078] [Comparative Example 1]
[0079] A composite composition of hydrogel and microspheres was prepared in the same manner as in Example 1 by changing the content of PCL microspheres to 5 wt% and, correspondingly, setting the content of cross-linked HA hydrogel to 95 wt%.
[0080] [Comparative Example 2]
[0081] A composite composition of hydrogel and microspheres was prepared in the same manner as in Example 1 by changing the content of PCL microspheres to 30 wt% and, correspondingly, setting the content of cross-linked HA hydrogel to 70 wt%.
[0082] [Comparative Example 3]
[0083] A hyaluronic acid filler was prepared in the same manner as in Example 1, except that it did not contain PCL microspheres.
[0084] [Comparative Example 4]
[0085] A hyaluronic acid filler was prepared in the same manner as in Example 1, except that a commercially available CaHA (calcium) filler was used.
[0086] The processing conditions for each example and comparative example are as shown in Table 1.
[0087] Treatment group Processing conditions Example 1 PCL microsphere (15 wt%) and cross-linked HA (85 wt%) composite scaffold Comparative Example 1 PCL microspheres (5 wt%) and cross-linked HA (95 wt%) composite scaffold Comparative Example 2 PCL microsphere (30 wt%) and cross-linked HA (70 wt%) composite scaffold Comparative Example 3 Cross-linked HA filler Comparative Example 4 CaHA (calcium) filler
[0088] [Experimental Example 1] Comparison of Rheological Properties and Injectability of Compositions According to PCL Microsphere Content
[0089] The basis for the design of the physical properties of the composition of the present invention is concretized through the evaluation of rheological storage modulus (G') and injection force. The storage modulus at 1 Hz was measured using a rheometer for the compositions of Example 1 and Comparative Examples 1 and 2 under conditions of 25°C, and the maximum load (N) was measured using a universal testing machine (UTM) when the compositions of Example 1 and Comparative Examples 1 and 2 were filled into a 1 mL syringe as a sample and extruded at a speed of 10 mm / min with a 23 G cannula attached.
[0090] The measurement results are as shown in Table 2.
[0091] Example 1 Comparative Example 1 Comparative Example 2 Storage modulus (Pa) 410 150 850 Injection pressure (N) 12.5 6 28
[0092] Figure 2 is a graph showing the results of Table 2. Comparative Example 1, containing 5% PCL, has a storage modulus of 150 Pa, which is too low, making it difficult to structurally support the cavity after the mammotome procedure and raising concerns that it may spread easily. Comparative Example 2, containing 30% PCL, has a high density of PCL particles, requiring an excessive force of more than 25 N during injection, making it difficult for the operator to inject precisely. Additionally, the storage modulus is excessively high at 850 Pa, which increases the likelihood of a hard foreign body sensation when touched after the procedure and appears unnatural.
[0093] Example 1 (PCL 15%) containing 15% PCL showed an injection pressure of 12.5N, which is suitable for general filler procedures, exhibiting excellent ease of procedure, and a storage modulus of approximately 410 Pa, which represents an optimal elastic range that can maintain appropriate volume within breast tissue while minimizing foreign body sensation.
[0094] [Experimental Example 2] Evaluation of Radiolucency
[0095] Example 1, Comparative Example 3, and Comparative Example 4 were injected into a breast tissue model (Phantom), and mammography (X-ray) was performed.
[0096] The experimental results are as shown in Figure 3. Comparative Example 4, which used a commercial CaHA filler, is a radiopaque material and appears as high-density white dots (radio-opaque), making it difficult to distinguish from microcalcification, whereas the composition of the present invention showed radiotransparency similar to surrounding phantom tissue, confirming that it does not cause interference with imaging diagnosis.
[0097] [Experimental Example 3] Evaluation of Cohesion and Anti-migration
[0098] Cohesion and mobility were evaluated by performing a stirring test in physiological saline.
[0099] The experimental results are as shown in Figure 4. Comparative Example 3, which used a commercial HA 100% filler, was easily loosened and dispersed upon stirring, whereas the composition of the present invention exhibited strong cohesive force due to the support effect of PCL microspheres and firmly maintained its initial lump shape, thereby confirming that it can suppress adverse effects of migration within the body.
[0100] [Experimental Example 4] Evaluation of In vivo Tissue Regeneration and Volume Maintenance Efficacy
[0101] In vivo tissue regeneration and volume maintenance were evaluated by analyzing tissues at 12 weeks after subcutaneous injection in experimental mice using Masson's Trichrome staining.
[0102] Masson's Trichrome staining is a three-color staining method used to distinguish major components within tissues. Generally, collagen fibers are stained in blue or green hues, muscle and cytoplasm in red hues, and nuclei in black or dark blue hues to create a contrasting effect, allowing for the visual assessment of the degree of fibrosis and collagenogenesis.
[0103] The experimental results are shown in Fig. 5. In Comparative Example 3, most of the HA was absorbed and the volume decreased, whereas in the composition of the present invention, new collagen fibers (blue) were densely formed between the PCL microspheres, maintaining the overall volume. This indicates that the present invention has the effect of inducing tissue regeneration beyond being a simple filler.
Claims
Claim 1 An injectable composite support composition comprising a hydrogel matrix made of cross-linked hyaluronic acid and biodegradable polymer microspheres comprising one or more selected from the group consisting of polycaprolactone (PCL), polylactic acid (PLA), polyglycolic acid (PGA), poly(lact-co-glycolic) acid (PLGA), polydioxanone (PDO), polytrimethylene carbonate (PTMC), and copolymers thereof, wherein the diameter of the biodegradable polymer microspheres is 10 μm to 100 μm, and the biodegradable polymer microspheres exist in a dispersed state within the hydrogel matrix, wherein the composition comprises the biodegradable polymer microspheres in a range of 8% to 28% by weight relative to the total weight of the composition, and wherein the storage modulus (G') of the composition is in the range of 200 Pa to 800 Pa at 25°C, and wherein the composition exhibits radiotransparency in X-ray imaging. Claim 2 In paragraph 1, The above composition is an injectable composite scaffold composition that is injected into a defect site within breast tissue to fill the defect space, prevent sunken deformation, and induce self-tissue regeneration. Claim 3 In claim 1, the average molecular weight of the hyaluronic acid serving as the raw material for the cross-linked hyaluronic acid hydrogel is 0.5 MDa to 5.0 MDa Characterized by being a range Injectable composite support composition . Claim 4 In claim 1, the hyaluronic acid concentration of the cross-linked hyaluronic acid hydrogel is 5 mg / mL to 50 mg / mL Characterized by being a range Injectable composite support composition . Claim 5 delete Claim 6 In claim 1, the biodegradable polymer microsphere has a diameter 15 µm to 80 µm Characterized by being a spherical particle of the range Injectable composite support composition . Claim 7 delete Claim 8 In claim 1, the storage modulus (G') of the composition is at 25°C 400 Pa to 500 Pa Characterized by being a range Injectable composite support composition . Claim 9 In claim 1, the injection pressure is characterized in that when the above composition is filled with a sample in a 1 mL syringe and then extruded at a speed of 10 mm / min with a 23G cannula attached, the injection pressure is in the range of 8 N to 25 N. Injectable composite support composition .
Citation Information
Patent Citations
Hyaluronic Acid Compositions Containing Slowly Resorbable Polymers
US20220362437A1
